Differential diagnosis of ovarian neoplasm using contrast-enhanced ultrasound (clinical case) - N. Е. Safonova; N. М. Podzolkova; V. В. Osadchev; K. V. Babkov; I. Е. Fadeev (Лечащий Врач)
Diagnosis of ovarian neoplasms is one of the most difficult tasks in practical gynecology. In the area of the uterine appendages, both true tumors and tumor-like formations, as well as formations emanating from other organs of the abdominal cavity and small pelvis, can be located. Difficulties in the timely diagnosis of ovarian tumors lie in the absence of clinically expressed precancerous conditions and are aggravated by their complex pathogenesis. Due to the high risk of malignant rebirth of ovarian tumors and the inability to diagnose a precancerous condition, the problem of early detection of ovarian neoplasm seems to be the most relevant. Today, it is possible to classify a tumor as malignant and determine its stage only after surgical operation with subsequent histological examination of removed tissues. Further patient treatment are based on the results of a histological examination. The description of this clinical case may help to enhance the capabilities and knowledge of practitioners in their approach to differential diagnosis of ovarian tumors. Patient N., 33 years old in April 2020, turned to the hospital named after D.D. Pletnev in the direction from the women's consultation with a diagnosis: left ovarian cyst, pain syndrome. The subject of interest of this clinical case is the differential diagnosis of ovarian neoplasm. Taking into account the results of the preliminary examination, we can think about a malignant ovarian neoplasm, relapse of the ovarian dermoid cyst, ovarian fibroma, uterine myoma with subserosal localization of node. That’s why an important task is to create optimal algorithms for diagnosing and routing patients in case of suspicion of an adnexal tumor. Modern diagnostics of ovarian tumors cannot be based on one research method, but requires a whole range of diagnostic measures that determine the tactics of introducing patients in each specific case.